It is for a different strain - The Star, (2009)
In response to the question raised by S. Param of Ipoh ("Take care in vaccine trials" - NST, June 11), it is worth nothing that the H1N1 vaccine that will be used in the trial on pigs is of a different strain that that of the novel H1N1 influenza A that is currently causing outbreaks among humans worldwide.